ANALISIS PRODUCT MAPPING DAYA SAING EKSPOR PRODUK PRIMER INDONESIA DAN CHINA - Sabaruddin, Sulthon Sjahril (LPPM Universitas Terbuka, 2015)
This research attempts to analyze the mapping competition of the Indonesian and Chinese primary products in order to identify and map the strengths and weaknesses of Indonesian products vis-à-vis China. To examine this, the study uses tools such as the SMART Model (Software for Market Analysis and Restrictions on Trade), Social Accounting Matrix 2008 (SAM 2008), Normalized Revealed Comparative Advantage (NRCA) and the Product Mapping. The results of the competition analysis found that Indonesia which rely on the export of primary products, in overall it is predicted to win the competition against China as the Indonesian primary products have better competitiveness than China. However, in the future, the competition will be fiercer, therefore, Indonesia should make efforts to improve further the competitiveness of Indonesian exports. Penelitian ini dimaksudkan untuk mengevaluasi peta persaingan produk primer Indonesia dan China guna mengidentifikasi dan memetakan kekuatan dan kelemahan produk Indonesia dalam persaingan dengan produk-produk primer asal China. Guna menelaah studi ini, beberapa perangkat dimanfaatkan yakni SMART Model (Software for Market Analysis and Restrictions on Trade), Sistem Neraca Sosial Ekonomi 2008 (SNSE 2008), Normalized Revealed Comparative Advantage (NRCA) dan Product Mapping. Hasil analisis peta persaingan kedua negara, Indonesia yang mengandalkan ekspor produk primer diperkirakan secara keseluruhan unggul dibandingkan produk primer dari China karena Indonesia memiliki daya saing yang lebih baik dibandingkan China. Namun demikian, perlu diperhatikan bahwa persaingan ke depan akan berlangsung semakin ketat, oleh karena itu Indonesia perlu melakukan upaya untuk meningkatkan daya saing ekspor Indonesia.